"Technologies of Reflexivity": Generating Biopolitics and Institutional Risk to Supplement Global Public Health Security. (6th December 2017) - FLEAR, Mark L
Abstract: Critiques of global public health security (GPHS) and proposed solutions tend to overlook the potential of the individuals and groups that are subject to and governed by GPHS – "the governed" – to contribute their "on the ground" knowledge and experience to decision-making in order to improve regulatory responses. This article argues for the development of a more reflexive approach as a way of ensuring the epistemic integration of these knowledges with the scientific-technical knowledges that currently dominate decision-making processes. I identify human rights as the conceptual lens that is most likely to enable reflexivity by the governed and regulators, and understanding and communication between them. The governed can use perceived or actual breaches of human rights to articulate "on the ground" knowledges as institutional risks to reputation and standing and, in turn, threaten the production and legitimation of organisational identity, socio-political orders and projects of rule. The particular sensitivity of regulators to these risks could compel epistemic integration. This more reflexive approach to GPHS promises to improve the knowledge base, efficacy, accountability and legitimacy of decision-making at multiple levels: WHO, EU, national and "on the ground".